Price Setting and Price Adjustment in Some European Union Countries - Daniel Levy; Frank Smets (Managerial and Decision Economics, 2010)
This introductory essay briefly summarizes the 11 empirical studies of price setting and price adjustment that are included in this special issue. The studies, which use data from several European countries, were conducted as part of the European Central Bank's Inflation Persistence Network.
Keywords: D21; D40; E12; E31; E50; E52; E58; L11; L16; M20; M30; 330; Price Rigidity; Price Flexibility; Cost of Price Adjustment; Menu Cost; Managerial and Customer Cost of Price Adjustment; Pricing; Price System; Price Setting; New Keynesian Economics; Store-Level Data; Micro-Level Data; Product-Level Data